Entre mitos e verdades : o impacto do discurso bolsonarista na Política de Assistência Social - Constant, Clarissa Constant de (2023)
Since December 2019, we have been experiencing humanity's biggest health crisis, with thousands of deaths in the world, with 691,000 in Brazil alone (BRASIL, 2022). Directing specifically to the national reality, our country is going through a period of denialism in the face of the COVID-19 pandemic, in which former president Jair Bolsonaro minimized the potential of the virus, in addition to not encouraging adherence to vaccination due to personal interests. political and economic. In addition, the Bolsonaro government presented a neoliberal agenda that strongly contributed to the dismantling of public policies, causing the already existing social inequalities to worsen and, with that, the innumerable expressions of the social issue, such as hunger, unemployment, the difficulty of accessing health and education, the precariousness of work, domestic violence, among others, were enhanced. That said, the present study analyzed whether the challenges for Social Work, in the operationalization of the social assistance policy and in the context of a pandemic, were related to the Bolsonaro government's discourse. From this, we seek to contribute with subsidies to strengthen the network and the management of this Policy. To this end, a bibliographical review and a semi-structured interview script were carried out, with an intentional sample of seven Social Workers, workers in the basic protection network in the city of Porto Alegre and active during the pandemic period. The collected data were analyzed from the critical analysis of the speech, in van Dijk's perspective, through which it was found that the inferences that the Bolsonaro government's speeches caused in the professional practice of Social Workers, active in the basic protection network of Porto Alegre. Finally, the discourse of the Bolsonarist government, which follows the logic of capital, ends up accentuating even more conservatism, which strongly contributes to the increase in social inequalities.